A Basic Review of the Preliminary Evidence That COVID-19 Risk and Severity Is Increased in Vitamin D Deficiency - Benskin, Linda L. (Frontiers in Public Health, 2020)
As the attention of the world has been riveted upon the growing Covid-19 pandemic, many researchers have written brief reports supporting the hypothesis that vitamin D deficiency is related to the incidence and severity of Covid-19. A literature search was performed on PubMed and Google Scholar, with Google searches providing additional sources. The research evidence supporting a link between vitamin D deficiency and Covid-19 risks is already quite strong. Vitamin D deficiency can help explain why each high risk group is more likely to develop severe Covid-19, why certain areas of the world have more fatalities, and why Covid-19 produces a cytokine storm in high-risk individuals. The evidence strongly supports vitamin D supplements during the Covid-19 pandemic for people who are less able to synthesize it from the sun. The review of the literature found that prophylactically correcting possible vitamin D deficiency with 2000IU of vitamin D daily is extremely safe.